Effect of angiotensin receptor-neprilysin inhibitor on atrial electrical instability in atrial fibrillation - Zhu, Tianyu; Zhang, Wenchao; Yang, Quan; Wang, Ning; Fu, Yuwei; Li, Yan; Cheng, Guanliang; Wang, Liang; Zhang, Xian; Yao, Hongying; Sun, Xinghe; Chen, Yu; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background & Objective: Around 33.5 million patients suffered from atrial fibrillation (AF), causing complications and increasing mortality and disability rate. Upstream treatment for AF is getting more popular in clinical practice in recent years. The angiotensin receptor-neprilysin inhibitor (ARNI) is one of the potential treatment options. Our study aimed to investigate the effect of ARNI on atrial electrical instability and structural remodeling in AF. Results: Clinical data showed that the atrial arrhythmia rate at 24-week was significantly lower in ARNI group compared to ARB group (P<0.01), and ARNI was independently associated with a lower atrial arrhythmia rate (P<0.05) at 24-week in multivariate regression logistic analysis. In the animal experiment, ARNI group had a higher atrial electrical stability score and a shorter AF duration in the EPS compared to Control and ARB group (P<0.05). In the left atrium voltage mapping, ARNI group showed less low voltage and disordered zone compared to Control and ARB group. Compared to Control group, right atrium diameter (RAD), left ventricle end-diastolic volume index (LVEDVI), E/A and E/E’ were lower in ARNI group (P<0.05) at the 8-weeks follow-up, while left atrium ejection fraction (LAEF) and left ventricle ejection fraction (LVEF) were higher (P<0.01). Compared to ARB group, LVEF was higher in ARNI group at the 8-week follow-up (P<0.05). ARB and ARNI group had a lower ratio of fibrotic lesions in the left atrium tissues compared to Control group (P<0.01), but no difference was found between the ARB and the ARNI group. Conclusion: ARNI could reduce atrial electrical instability in AF in comparison with ARB in both retrospective study and animal experiment.